Preparation method of water-based copper-doped NiOx nano material and product and application of water-based copper-doped NiOx nano material

By using organic ligands such as alcohol ethers and controlling pH values ​​in copper-doped NiOx nanomaterials, the aqueous copper-doped NiOx nanomaterials were prepared, which solved the problems of poor dispersion in water and unstable hole conductivity, and significantly improved the performance and storage performance of photovoltaic devices.

CN119677302AActive Publication Date: 2025-03-21XIAN POLYMER LIGHT TECH
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411833367.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The poor dispersion of existing copper-doped NiOx nanomaterials in water leads to unstable hole mobility of photovoltaic devices, poor hydrophilicity, easy to accumulate and sink, affecting the light conversion rate of the device.

Method used

Organic ligands such as alcohol ether, alcohol amine, glycol, polyethylene glycol are mixed with nickel and copper salts, and the pH value is controlled between 8-12. Water-based copper-doped NiOx nanomaterials are prepared by calcining and ball milling to form a core-shell structure to improve dispersion and conductivity.

Benefits of technology

It significantly improves the dispersion of copper-doped NiOx nanomaterials in water, enhances its hole conductivity and hydrophilicity, improves the photoconversion and storage performance of photovoltaic devices, and at the same time, the process is environmentally friendly and avoids pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119677302A_ABST
    Figure CN119677302A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of solar cells, and particularly relates to a preparation method of a water-based copper-doped NiOx nano-material and a product and application of the water-based copper-doped NiOx nano-material, a NiOx shell layer grows on the surface of the prepared Cu: NiOx nano-material, one or more of alcohol ether, alcohol amine, glycol and polyethylene glycol are used as surface ligands of the nano-material, the number of carbon chains is limited to be 2-4, and the water-based copper-doped NiOx nano-material is prepared. The copper-doped nickel oxide dispersion liquid is used for providing water-based groups (-OH and-NH2), aims to be dispersed in water without influencing the conductivity of the copper-doped nickel oxide dispersion liquid, and also can provide binding sites chelated with In and Sn on ITO (Indium Tin Oxide), so that the copper-doped nickel oxide dispersion liquid has relatively high oxygen affinity, relatively good leveling property, excellent film-forming property, relatively good spreadability, adhesive strength and compactness on an FTO (Fluorine-doped Tin Oxide) substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solar cells and particularly relates to an aqueous copper-doped NiO x Preparation methods of nanomaterials, their products and applications. Background Art

[0002] With the continuous development of science and technology, perovskite solar cells have the advantages of high ultimate conversion efficiency, low production cost, simple preparation process, high flexibility, etc., which makes them applicable to photovoltaic power generation and other fields, and have broad development prospects. x As a commonly used hole transport layer material in inverse perovskite solar cells, it has the advantages of low cost and low synthesis temperature, so it is widely used in photovoltaic devices.

[0003] However, conventional Cu-doped NiO x Nanomaterials have poor dispersibility in water and are prone to flocculation. Secondly, hole mobility is affected by the concentration of trivalent Ni, the concentration of Cu doping, and the concentration ratio of Cu(2+) / Cu(1+), which is not stable enough. Due to poor dispersibility, the affinity of the nanomaterials on ITO (tin-doped indium oxide) and FTO (Fluorine-doped Tin Oxide) substrates is relatively low when preparing photovoltaic devices. The spin-coated thin films are prone to problems such as uneven film surface, large leakage current, and increased series resistance, which ultimately reduce the light conversion rate of the device. These problems greatly limit its application in the field of perovskite solar cells. Summary of the invention

[0004] The purpose of the present invention is to provide a kind of aqueous copper-doped NiO x The preparation method of nanomaterials and its products and applications are used to solve the problems existing in the prior art of copper-doped NiO x Nanomaterials have low hole conductivity, poor hydrophilicity, are easily reduced, and the photoconversion efficiency of the devices made from them is low.

[0005] A kind of aqueous copper-doped NiO x The method for preparing a nano material comprises the following steps:

[0006] S1. mixing one or more of alcohol ether, alcohol amine, glycol, polyethylene glycol and a solvent to form a first reaction system;

[0007] S2. Under a 10-30°C environment, the nickel salt, the copper salt and the first reaction system are mixed to obtain a second reaction system;

[0008] S3. Add 10%-50% of base by mass to the second reaction system, control the pH to 8-12, and react for 0.2-24h to obtain Cu:Ni(OH) 2 Sol dispersion system;

[0009] S4. Centrifuge the above Cu:Ni(OH) 2 Sol dispersion system, washed with water several times until no anions are present;

[0010] S5. Cu:Ni(OH) 2 The sol was calcined at 200℃-300℃ for 1-24h to obtain black Cu:NiO x calcined body;

[0011] S6.Cu:NiO x The calcined body was ball milled in a ball mill for 0.5-24h to obtain Cu:NiO x Nano powder;

[0012] S7.Cu:NiO x The nanopowder was ultrasonicated for 0.1-10h under an ultrasonic probe to obtain Cu:NiO x Nanoparticles in water.

[0013] Furthermore, after step S3, the method further comprises: adding the Cu:Ni(OH) obtained in step S3 to the Cu:Ni(OH) 2 Add nickel salt and alkali to the sol dispersion system, control the pH value at 8-12, and react for 0.5-12 hours.

[0014] Furthermore, the alcohol ether described in S1 is a straight-chain alcohol ether with a carbon chain number of 3-5; the alcohol amine is a straight-chain alcohol amine with a carbon chain number of 2-5; the polyol is a glycol with a carbon chain number of 2-6; and the solvent is one of water, methanol and ethanol.

[0015] Furthermore, the volume ratio of the total volume of the alcohol ether, alcohol amine, glycol, and polyethylene glycol to the solvent in the first reaction system is: (0.1-0.5):1.

[0016] Furthermore, in terms of the amount of substance, the overall feed ratio of the nickel salt and the alkali in S3 is 1:(0.5-3).

[0017] The aqueous copper-doped NiO prepared by the above-mentioned preparation method x Nanomaterial, with copper-doped NiO inside x The outside is an organic ligand, and the organic ligand is one or more of alcohol ether, alcohol amine, glycol, and polyethylene glycol.

[0018] Aqueous copper-doped NiO prepared by another preparation method as described above x Nanomaterial, with copper-doped NiO inside xAs the core, there is another layer of NiO outside the core x As shell, NiO x The outer surface of the semiconductor is an organic ligand, which is one or more of alcohol ether, alcohol amine, glycol, and polyethylene glycol. The semiconductor configuration is a type I structure, where the conduction band bottom and valence band top of one material are both within the bandgap width of another material.

[0019] Furthermore, the organic ligand content accounts for 5%-30% of the total weight of the entire nano material, the particle size of the nano material is 3-10nm, and the band gap is 3.6eV-4.0eV.

[0020] Furthermore, in terms of mass, the copper-doped NiO x The ratio of Ni:Cu in nanomaterials is 1:(0.01~0.5), NiO x The invention comprises nickelous oxide and nickelous oxide, wherein the molar ratio of trivalent nickel to divalent nickel is 0.1-1.

[0021] As mentioned above, the aqueous copper-doped NiO x Application of nanomaterials as hole transport layer materials in perovskite solar cells.

[0022] The beneficial effects of the present invention are as follows:

[0023] The present invention uses one or more of alcohol ether, alcohol amine, glycol, and polyethylene glycol as the surface ligand of the nanomaterial, and limits the carbon chain number to 2-4 to provide water-based groups (-OH, -NH 2 ), the purpose of which is to be dispersible in water without affecting its conductivity, and to provide binding sites for chelating with In and Sn on ITO, so that the copper-doped nickel oxide dispersion on the FTO substrate has higher oxygen affinity, better leveling, excellent film-forming properties, better spreadability, adhesion, and compactness;

[0024] The copper doping in the nickel oxide of the present invention can effectively reduce the excitation energy level of the majority holes in the material; secondly, the prepared core-shell structure nanomaterial not only optimizes the energy level structure, but also significantly enhances the dispersibility of the material in water, thereby improving the device performance while also effectively improving the storage performance of the material. The entire reaction is carried out at room temperature, which is green, environmentally friendly and pollution-free, avoiding the occurrence of danger. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The Cu:NiO prepared by the present invention x @NiO x Schematic diagram of the core-shell structure.

[0026] Figure 2 The Cu:NiO prepared by the present invention x@NiO x TEM image of nanoparticles (Transmission Electron Microscope image).

[0027] Figure 3 The Cu:NiO prepared by the present invention x @NiO x Nanoparticle XRD pattern (X-Ray Diffraction pattern). DETAILED DESCRIPTION

[0028] The technical solution of the present invention will be further described below through embodiments and drawings.

[0029] The present invention first provides an aqueous copper-doped NiO x The method for preparing a nano material comprises the following steps:

[0030] S1. mixing one or more of alcohol ether, alcohol amine, glycol, polyethylene glycol and a solvent to form a first reaction system;

[0031] S2. Under a 10-30°C environment, the nickel salt, the copper salt and the first reaction system are mixed to obtain a second reaction system;

[0032] S3. Add 10%-50% of base by mass to the second reaction system, control the pH to 8-12, and react for 0.2-24h to obtain Cu:Ni(OH) 2 Sol dispersion system;

[0033] S4. Centrifuge the above Cu:Ni(OH) 2 Sol dispersion system, washed with water several times until no anions are present;

[0034] S5. Cu:Ni(OH) 2 The sol was calcined at 200℃-300℃ for 1-24h to obtain black Cu:NiO x @NiO x calcined body;

[0035] S6.Cu:NiO x The calcined body was ball milled in a ball mill for 0.5-24h to obtain Cu:NiO x @NiO x Nano powder;

[0036] S7.Cu:NiO x The nanopowder was ultrasonicated for 0.1-10h under an ultrasonic probe to obtain Cu:NiO x @NiO x Nanoparticles in water.

[0037] In order to obtain the core-shell structure Cu:NiO x @NiO x , Cu:Ni(OH) obtained from S3 2 Add nickel salt and alkali to the sol dispersion system, control the pH at 8-12, and react for 0.5-12h to obtain Ni(OH) 2 Shell layer; then proceed to the subsequent steps.

[0038] The present invention comprises two structures of aqueous copper-doped NiO x Nanomaterials, one of which is made of copper-doped NiO x The outside is an organic ligand, which is one or more of alcohol ether, alcohol amine, glycol, and polyethylene glycol. The inside of the second structure is copper-doped NiO x As the core, there is another layer of NiO outside the core x As shell, NiO x The outer surface of the semiconductor is an organic ligand, which is one or more of alcohol ether, alcohol amine, glycol, and polyethylene glycol. The semiconductor configuration is a type I structure, where the conduction band bottom and valence band top of one material are both within the bandgap width of another material.

[0039] The alcohol ether described in S1 is a straight-chain alcohol ether with a carbon chain number of 3-5. For example, one of ethylene glycol methyl ether, ethylene glycol ethyl ether, ethylene glycol propyl ether, propylene glycol methyl ether, and propylene glycol ethyl ether. The alcohol amine is a straight-chain alcohol amine with a carbon chain number of 2-5, for example, one of ethanolamine, propanolamine, butanolamine, and pentanolamine. The polyol is a glycol with a carbon chain number of 2-6, for example, one of ethylene glycol, diethylene glycol, and triethylene glycol.

[0040] The nickel salt in S2 and S4 can be selected from but not limited to nickel nitrate and its hydrate, nickel chloride and its hydrate, nickel acetate and its hydrate, nickel sulfate and its hydrate, nickel bromide and its hydrate, nickel acetylacetonate and its hydrate, nickel dibutyldithiocarbamate, nickel diethyldithiocarbamate, nickel oxalate, nickel phosphate, nickel xanthate, nickel ethylenediaminetetraacetic acid, nickel isopropoxide, nickel 8-hydroxyquinoline, nickel stearate, nickel hypophosphite and its hydrate, nickel fluoride, basic nickel carbonate, nickel perchlorate, nickel benzoate, nickel thiocyanate, and nickel trifluoromethanesulfonate.

[0041] The copper salt in S2 can be selected from but not limited to copper nitrate and its hydrate, copper chloride and its hydrate, copper acetate and its hydrate, copper sulfate and its hydrate, copper bromide and its hydrate, copper acetylacetonate and its hydrate, dibutyl copper dithiocarbamate, diethyl copper dithiocarbamate, copper oxalate, copper phosphate, copper xanthate, copper citrate, copper ethylenediaminetetraacetate, and 8-hydroxyquinoline copper.

[0042] The alkali in S3 can be selected from but not limited to one or more of ammonia water, sodium hydroxide, potassium hydroxide, and tetramethylammonium hydroxide.

[0043] According to another aspect of the present invention, a perovskite solar cell is provided, comprising an anode, a hole transport layer, a light absorbing layer, an electron transport layer and a cathode, wherein the hole transport layer is made of the above copper-doped NiO x The nanoparticle aqueous dispersion is prepared by one of spin coating, printing, spray coating and blade coating.

[0044] Embodiment 1

[0045] The following is a shell-free structure of Cu:NiO x The synthesis of nanomaterials, where ethanolamine is attached as a surface ligand to the surface of copper-doped nickel oxide nanoparticles, includes the following steps:

[0046] S1. Mix 10 ml of ethanolamine with 1 L of water to form a first reaction system;

[0047] S2. At 20°C, 0.25 mol nickel nitrate, 0.01 mol copper nitrate and the first reaction system are mixed to obtain a second reaction system;

[0048] S3. Add 4 mol / L NaOH to the second reaction system, control the pH at 10, and react for 2 h to obtain Cu:Ni(OH) 2 Green sol dispersion system;

[0049] S4. Centrifuge the above Cu:Ni(OH) 2 Sol dispersion system, washed with water three times until nitrate ions were completely washed away;

[0050] S5. Cu:Ni(OH) 2 The sol was calcined at 280℃ for 2h to obtain black Cu:NiO x calcined body;

[0051] S6.Cu:NiO x The calcined body was ball milled in a ball mill for 12 h to obtain Cu:NiO x Nano powder;

[0052] S7.Cu:NiO x The nanopowder was ultrasonicated for 1 h under an ultrasonic probe to obtain Cu:NiO x Nanoparticles in water.

[0053] Embodiment 2

[0054] The following is the core-shell structure of Cu:NiO x @NiO xNanomaterial synthesis, ethanolamine, ethylene glycol methyl ether as surface ligands connected to the surface of copper-doped nickel oxide nanoparticles, including the following steps:

[0055] S1. Mix 8 ml of ethanolamine, 2 ml of ethylene glycol methyl ether and 1 L of ethanol to form a first reaction system;

[0056] S2. At 15°C, 0.3 mol nickel chloride, 0.008 mol copper chloride and the first reaction system are mixed to obtain a second reaction system;

[0057] S3. Add 10% ammonia water to the second reaction system, control the pH at 9, and react for 1 hour to obtain Ni(OH) 2 Sol dispersion system;

[0058] In order to obtain the core-shell structure Cu:NiO x @NiO x , to the above Cu:Ni(OH) 2 Add 0.05 mol nickel chloride to the sol dispersion system, react for 0.5 h, then add 10% ammonia water, control the pH at 10, and react for 0.5 h to obtain Ni(OH) 2 Shell;

[0059] S4. Centrifuge the above Cu:NiO x @NiO x Sol dispersion system, wash with water three times until the ammonium ions are completely washed away;

[0060] S5. Cu:Ni(OH) 2 The sol was calcined at 290℃ for 3h to obtain black Cu:NiO x calcined body;

[0061] S6.Cu:NiO x The calcined body was ball milled in a ball mill for 3 h to obtain Cu:NiO x Nano powder;

[0062] S7.Cu:NiO x The nanopowder was ultrasonicated for 0.5 h under an ultrasonic probe to obtain Cu:NiO x Nanoparticles in water.

[0063] Embodiment 3

[0064] The following is the core-shell structure of Cu:NiO x @NiO x Nanomaterial synthesis, n-propanolamine, polyethylene glycol 200, ethylene glycol as surface ligands connected to the surface of copper-doped nickel oxide nanoparticles, including the following steps:

[0065] S1. Mix 10 ml of n-propanolamine, 2 ml of polyethylene glycol 200, 1 ml of ethylene glycol and water to form a first reaction system;

[0066] S2. At 30°C, 0.3 mol nickel sulfate, 0.006 mol copper sulfate and the first reaction system are mixed to obtain a second reaction system;

[0067] S3. Add 4 mol / L KOH to the second reaction system, control the pH at 11, and react for 1 h to obtain Cu:Ni(OH) 2 Sol dispersion system;

[0068] In order to obtain the core-shell structure Cu:NiO x @NiO x , to the above Cu:Ni(OH) 2 Add 0.04 mol nickel sulfate and 0.006 mol copper sulfate to the sol dispersion system, react for 0.5 h, then add 4 mol / L KOH, control the pH at 10, and react for 0.5 h to obtain Ni(OH) 2 Shell;

[0069] S4. Centrifuge the above Cu:Ni(OH) 2 Sol dispersion system, washed with water three times until sulfate ions were eluted;

[0070] S5. Cu:Ni(OH) 2 The sol was calcined at 250℃ for 3.5h to obtain black Cu:NiO x calcined body;

[0071] S6.Cu:NiO x The calcined body was ball milled in a ball mill for 9 h to obtain Cu:NiO x Nano powder;

[0072] S7.Cu:NiO x The nanopowder was ultrasonicated for 1.5 h under an ultrasonic probe to obtain Cu:NiO x Nanoparticles in water.

[0073] Provided is a solar perovskite cell device, the manufacturing method of which comprises the following steps: spin coating a copper-doped nickel oxide nanomaterial aqueous dispersion in an embodiment on an ITO anode layer, and then annealing at 120° C. for 30 min to form a hole transport layer; spin coating a perovskite solution on the hole transport layer as a carrier to form an absorption layer; spin coating an isopropanol solution of zinc oxide on the absorption layer, and forming an electron transport layer after drying; and finally evaporating an Au cathode electrode layer, and encapsulating to form a perovskite solar cell device.

[0074] Comparative Example 1

[0075] Conventional copper-doped NiO x Preparation, comprising the following steps:

[0076] S1. At 25°C, 0.3 mol nickel nitrate, 0.006 mol copper nitrate and 1 L water were mixed to obtain a first reaction system;

[0077] S2. Add 0.6 mol of NaOH to the first reaction system and react for 2 h to obtain Cu:Ni(OH) 2 Sol dispersion system;

[0078] S3. Centrifuge the above Cu:Ni(OH) 2 Sol dispersion system, wash twice with water until nitrate ions are completely eluted;

[0079] S4. S4 was calcined at 280℃ for 1h to obtain black Cu:NiO x calcined body;

[0080] S5.Cu:NiO x The nanopowder was ultrasonicated for 1 h under an ultrasonic probe to obtain Cu:NiO x Nanoparticles in water.

[0081] Table 1: Comparison of device performance in various embodiments

[0082]

[0083]

[0084] Note: PCE is power conversion efficiency, TGA is thermogravimetric analysis.

[0085] It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. Aqueous copper-doped NiO x The method for preparing a nano material is characterized in that: The following steps are involved: S1. mixing one or more of alcohol ether, alcohol amine, glycol, polyethylene glycol and a solvent to form a first reaction system; S2. Under a 10-30°C environment, the nickel salt, the copper salt and the first reaction system are mixed to obtain a second reaction system; S3. Add 10%-50% of the base by mass to the second reaction system, control the pH at 8-12, and react for 0.2-24h to obtain a Cu:Ni(OH)2 sol dispersion system; S4. Centrifuge the Cu:Ni(OH)2 sol dispersion system and wash it several times until no anions are present; S5. Calcine the Cu:Ni(OH)2 sol of S4 at 200℃-300℃ for 1-24h to obtain black Cu:NiO x calcined body; S6.Cu:NiO x The calcined body was ball milled in a ball mill for 0.5-24h to obtain Cu:NiO x Nano powder; S7.Cu:NiO x The nanopowder was ultrasonicated for 0.1-10h under an ultrasonic probe to obtain Cu:NiO x Nanoparticles in water.

2. Aqueous copper-doped NiO according to claim 1 x The method for preparing nanomaterials is characterized by: After step S3, the method further includes: adding nickel salt and alkali to the Cu:Ni(OH)2 sol dispersion system obtained in S3, controlling the pH value at 8-12, and reacting for 0.5-12 hours.

3. Aqueous copper-doped NiO according to claim 1 or 2 x The method for preparing nanomaterials is characterized by: The alcohol ether described in S1 is a straight-chain alcohol ether with a carbon chain number of 3-5; the alcohol amine is a straight-chain alcohol amine with a carbon chain number of 2-5; the polyol is a glycol with a carbon chain number of 2-6; and the solvent is one of water, methanol and ethanol.

4. Aqueous copper-doped NiO according to claim 1 or 2 x The method for preparing nanomaterials is characterized by: The volume ratio of the total volume of the alcohol ether, alcohol amine, glycol and polyethylene glycol to the solvent in the first reaction system is: (0.1-0.5):

1.

5. Aqueous copper-doped NiO according to claim 2 x The method for preparing nanomaterials is characterized by: In terms of the amount of substance, the overall feed ratio of the nickel salt and the base in S3 is 1:(0.5-3).

6. Aqueous copper-doped NiO prepared by the preparation method according to claim 1 x Nanomaterials, characterized by: The nanomaterial is made of copper-doped NiO. x The outside is an organic ligand, and the organic ligand is one or more of alcohol ether, alcohol amine, glycol, and polyethylene glycol.

7. Aqueous copper-doped NiO prepared by the preparation method as claimed in claim 2 x Nanomaterials, characterized by: The nanomaterial is made of copper-doped NiO. x As the core, there is another layer of NiO outside the core x As shell, NiO x The outer surface of the semiconductor is an organic ligand, which is one or more of alcohol ether, alcohol amine, glycol, and polyethylene glycol. The semiconductor configuration is a type I structure, where the conduction band bottom and valence band top of one material are both within the bandgap width of another material.

8. Aqueous copper-doped NiO according to claim 6 or 7 x Nanomaterials, characterized by: The content of the organic ligand accounts for 5%-30% of the total weight of the entire nano material. The particle size of the nano material is 3-10nm and the band gap is 3.6eV-4.0eV.

9. Aqueous copper-doped NiO according to claim 6 or 7 x Nanomaterials, characterized by: In terms of mass, the copper-doped NiO x The ratio of Ni:Cu in nanomaterials is 1:(0.01~0.5), NiO x The invention comprises nickelous oxide and nickelous oxide, wherein the molar ratio of trivalent nickel to divalent nickel is 0.1-1.

10. Aqueous copper-doped NiO as claimed in claim 6 or 7 x Application of nanomaterials as hole transport layer materials in perovskite solar cells.

Citation Information

Patent Citations

  • Photoelectric device with colloid NiO nanocrystalline film as hole transport layer and manufacturing method thereof

    CN103840047A

  • Method for preparing copper-doped nickel oxide film under low temperature

    CN105280821A

  • NiO composite film, quantum dot light-emitting device and the preparation and application of the same

    CN107240624A

  • Band gap continuous adjustability and controllability-based inverted perovskite solar battery preparation method

    CN108023018A

  • Preparation method of NiO@SiO2@CoAl-LDH multistage core-shell catalyst

    CN112452328A